1997
DOI: 10.1159/000190133
|View full text |Cite
|
Sign up to set email alerts
|

Remnant-Like Particle Cholesterol May Indicate Atherogenic Risk in Patients on Chronic Hemodialysis

Abstract: Recently, involvement of remnant-like particle cholesterol (RLP-C) in atherosclerosis was reported, but this parameter has not been adequately investigated in hemodialysis (HD) patients. The present study investigated the relationship between the RLP-C level and total cholesterol (TC), triglycerides (TG), low density lipoprotein cholesterol (LDL-C), high density lipoprotein cholesterol (HDL-C), lipid peroxides (malone dialdehyde, MDA), apolipoprotein (Apo) A-I, and ApoB. In addition, the fractions of very low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…The low levels of plasma LDL seem to be typical in well-controlled CKD patients on maintenance HD in Japan. Plasma TG-rich lipoprotein remnant levels were high in HD patients, as previously reported [2,3]. Subfractionation of plasma LDL and HDL is usually performed by polyacrylamide gel electrophoresis, however the chemical composition of LDL and HDL subfractions cannot be determined by that method alone.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The low levels of plasma LDL seem to be typical in well-controlled CKD patients on maintenance HD in Japan. Plasma TG-rich lipoprotein remnant levels were high in HD patients, as previously reported [2,3]. Subfractionation of plasma LDL and HDL is usually performed by polyacrylamide gel electrophoresis, however the chemical composition of LDL and HDL subfractions cannot be determined by that method alone.…”
Section: Discussionsupporting
confidence: 64%
“…Plasma levels of triglyceride (TG)-rich lipoproteins and their remnants are known to be elevated in chronic kidney disease (CKD) patients on hemodialysis (HD) treatment [1,2,3]. Chylomicron and very low-density lipoprotein (VLDL) are TG-rich lipoproteins [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, in our study, serum RLP.C levels did not show any significant difference between the DM(+) group and DM(-) group. Oda et al [29] reported that serum RLP.C levels showed a positive correlation with serum levels of T.Cho, TG, LDL.Cho and VLDL.Cho in patients on HD. In our study, though serum TG levels in the DM(+) group were significantly higher than that in the DM(-) group, there were no significant differences in serum levels of T.Cho and LDL.Cho between the two groups (table 1).…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that LDL-cholesterol is a risk factor in cardiovascular disease, especially in Coronary Atherosclerotic (AS) [31,32]. Plasma levels of small, dense low-density lipoprotein (LDL) were reported to be increased in chronic kidney disease patients who undergoing HD [33,34].…”
Section: Discussionmentioning
confidence: 99%